Application of Biochar on Soil Improvement and Speciation Transformation of Heavy Metal in Constructed Wetland - Yuan Zhou; Xiaoqin Nie; Yao Zhao; Liqiu Zhang; Yatian Cheng; Cancan Jiang; Wenbin Zhao; Xiangchun Wang; Chao Yang (Biology)
The pyrolysis of sewage sludge into biochar, enhanced by incorporating agriculture waste rich in inorganic minerals and lignocellulosic compounds, provides an effective approach for achieving sludge-harmless treatment and resourceful utilization. In this study, sewage sludge and maize straw-based biochar (SMB) was prepared using the co-pyrolysis method, and the effects of different application ratios (0%, 1%, 3%, and 5%, w/w) of SMB on soil properties, ryegrass growth, microbial community structure, and Pb content and speciation in the contaminated soil of constructed wetlands were investigated. The results showed that SMB had a high carbon content (28.58%) and was rich in functional groups (e.g., -C-O, -C-N). The results indicated that increasing SMB dosage (0–5% w/w) in Pb-contaminated soil elevated soil pH from 6.40 to 7.93, cation-exchange capacity (CEC) from 30.59 to 79.03 cmol/kg (+158%), and organic carbon content by 65% (from 176.79 mg/kg to 107.3 mg/kg), while reducing available phosphorus and potassium by 20% and 30%, respectively, resulting in a 6% decline in ryegrass leaf length. SMB application enriched Pb-resistant bacteria (e.g., Sphingomonas abundance increased from 10.3% to 11.2%) and enhanced Pb immobilization. After 55 days, the total soil Pb increased by 33%, and the residual fraction Pb significantly increased by 7.3% to 21.7%, driven by functional group complexation, ion exchange, pH, and CEC improvements.